Shoot induction from Clinacanthus nutans (Burm.f.) lindau nodal in response to plant growth regulators and media composition on growth and antioxidant activities - Zainol, Nur Haida Syazana (2020)
Clinacanthus nutans, locally known as Sabah Snake Grass or Belalai Gajah, is one of the most promising medicinal plants in Malaysia’s herbal industry which posses numerous biological properties. Besides that, C. nutans extract produce a wide range of bioactive compounds including several specific compounds such as clinamides, entadamide, clinacoside and cycloclinacoside which only can be found in C. nutans extract. Due to high therapeutic potentials, C. nutans has been overexploited to satisfy the demands from pharmaceutical industry. Conventionally propagated of C. nutans by stem cutting is known to produce inconsistent secondary metabolites due to external factors in the environment such as climate, pests and diseases and fertilizer application. In the present study, plant tissue culture technique was adopted for shoot induction and biomass production of C. nutans for extraction of secondary metabolites. The nodal segments of C. nutans were used as explants and Murashige and Skoog (MS medium) was used as basal medium. The shoot induction of C. nutans nodal segments was carried out by supplementing the MS medium with cytokinins; 6-benzylaminopurine (BAP) or kinetin at concentration 4, 8, 12 and 16 μM each. The best treatment was recorded from MS medium supplemented with 12 μM BAP with 100% shoot induction, 1.30 shoots, 2.29 cm length of shoots, 4.78 leaves and 16.00 mg of leaves fresh weight after four weeks of incubation. In subsequent experiments, MS medium was supplemented with auxins; indole butyric acid (IBA) and naphthalene acetic acid (NAA) at concentration 2, 4, 6 and 8 μM each, followed by modification of MS medium strength into half, full and double strength. Lastly, sucrose concentration was tested at 20, 25, 30, 35, 40, 45 and 50 g/L, respectively. Based on the results obtained, full-strength MS medium supplemented with 12 μM BAP and 30 g/L sucrose without addition of auxin produced an optimum growth with 100% shoot induction, 1.67 shoots, 3.23 cm length of shoots, 7.33 leaves and 21.57 mg of leaves fresh weight after six weeks of incubation. Subsequently, analyses of phenolics content and antioxidant properties between tissue-cultured and conventionally propagated leaves were conducted. The leaves from both sources were extracted using aqueous at temperature 25 and 100ºC. In the study on phenolics content, the highest total polyphenols, phenolic acids and falvonoids content were recorded from 100ºC aqueous extract of tissue-cultured leaf with 2.77 mg GAE/g DW, 4.29 mg GAE/g DW and 21.76 mg RE/g DW, respectively. In antioxidant properties analysis, 100ºC aqueous extract of tissue-cultured leaf was exhibited the highest DPPH free radical scavenging activity (3.20 mg TE/g DW), ABTS scavenging activity (1.50 mg TE/g DW), ferric reducing antioxidant power (9.76 mg TE/g DW) and superoxide anion radical scavenging activity (53.74%). Meanwhile, the highest iron (II) chelating activity was recorded from 25ºC aqueous extract of conventionally propagated leaf with 69.24% chelating activity. In the present study, shoot induction from C. nutans nodal segments was successfully conducted and bioactive compounds analysis showed that tissue-cultured leaf was able to produce higher phenolics content and antioxidant properties compared to conventionally propagated leaf.